Integrated winter road maintenance management - New directions for cold regions research - Hinkka, V.; Pilli-Sihvola, E.; Mantsinen, H.; Leviakangas, Pekka; Aapaoja, A.; Hautala, R. (Elsevier, 2016)
The purpose of winter road maintenance is to reduce the negative effect of snow and ice on traffic. The current literature on winter maintenance practices is split into two segments: means of forecasting weather in order to plan proper winter maintenance, and optimization of maintenance operations. There is relatively little literature on the opportunities that real-time information, e.g., from maintenance vehicles, would offer for combining these two segments and taking the applied research and practice one step further. It seems, however, that the lack of operational solutions has so far limited empirical research in favour of analysing prospects that the ubiquitous technologies could offer for winter maintenance. Recent field tests show that the technical obstacles to obtaining real-time information from maintenance vehicles can be overcome. Thus it is possible to enhance the benefits of winter road maintenance operations considerably through new designs and architectures. Improving the efficiency of vehicle fleets by using real-time information is one of the first realizable steps. Based on the analysis of current winter road maintenance ecosystems in several countries, this paper suggests how to make effective use of the transparency that real-time information exchange between different actors can offer. Transparent real-time information enables re-engineering of the entire winter maintenance ecosystem and assists road authorities in setting more precise, and at the same time more diverse, objectives for winter maintenance. This also involves real-time monitoring of service providers' performance and realization of these objectives.